Integrating Tourism Villages Through Thematic Tourism Route Development: A Case Study in Bangka Island - Raksapati, Abadi; Akbar, Muhammad Dhaifan; Murdiyati, Fatma Indah (ASEAN Journal on Hospitality and Tourism, 2025)
Bangka Island, as one of the economic centres and the government hub of the Bangka Belitung Islands Province, plays a strategic role in fostering theregional self-suffiency. Bangka Island as the largest island in the Province of Bangka Belitung Islands has the largest population as well as an abundant potential resources for tourist attractions. To develop these potential reseorces into tourist attractions, the participation of host community is essential. The tourist village as a form of tourism destination should be able to play its function in optimising the various tourist attractions owned by the village by maximising existing human resources. Due to the limited human resources quality, tourist villages must collaborate with each otherin order to strengthen each other to develop their tourism products and addressing their respective shortcomings. This study tries to explore the element that can unite tourism villages on Bangka Island as a holistic tourism destination that offers variety of rural attractions. The findings show that tourism villages on Bangka Island have a common thread that can clustered tourism villages to be developed into several themes, whichthen can be used to foster several thematic tour packages that connect all the tourism villages. The recommended themes of Bangka Island tourism village development include Bangka Island Geotourism, Bangka Culture, Bangka Maritime Tourism, Bangka Typical Culinary Tourism, Animal Observation Tourism, and Bangka Typical Flora Observation Tourism.